Toward an integrated platform to support contract furniture industry. Issue 5 (2nd September 2016) - Mengoni, Maura; Peruzzini, Margherita; Bordegoni, Monica; Mecella, Massimo
ABSTRACT: The paper presents an integrated technological framework, which aims to make a step forward in contract furniture design methods and supporting web-enabling applications. The implementing platform enables the extensible and temporary cluster of companies to manage the entire contract furniture process. The main contribution regards the integration of different software modules into an overall system that exploits E-marketing Intelligence applications, 3D web-based tools and Augmented Reality techniques. Different user interfaces are implemented to accomplish the involved stakeholders needs and furniture development goals. GRAPHICAL ABSTRACT: